مدى عناية المحدثين بالقرائن العقلية في المنهج النقدي - Ili Dalila Binti Mohd Redzwan; Ahmed El-Mogtaba Bannga (البصيرة: مجلة الدراسات الإسلامية, 2023)
The opposing groups of ahl al-ḥadīth, such as the past Mu’tazilites, groups of thinkers in the present days, and also orientalists that wrote about the Sunnah, assumed that the methods applied by al-Muḥaddithūn in ḥadīth critism are not meticulous and elaborated, especially in matn (content) criticism, which, in their view, received an inadequate amount of attention, as opposed to their attention to the criticism of sanad (chains of narration). They deemed that matn criticism must be based solely on the outlook of ʿaql (reasoning) to regard the appropriateness of a ḥadīth. Therefore, this study aims to address the extent of attention designated by al-Muḥaddithūn towards rational evidence in ḥadīth criticism and to highlight their directive in employing reasoning to criticize the chains of narration and the content of a ḥadīth. The research adopts inductive and analytical approaches while presenting the employment of reasoning by al-Muḥaddithūn in ḥadīth criticism. Some of the findings of the research lie in several observations: that the methods applied by al-Muḥaddithūn in ḥadīth criticism are based upon solid and profound principles of reasoning that are well-accepted by sensible people. And that all sound ḥadīth came from the Prophet pbuh, which has gone through the processes of criticism established by al-Muḥaddithūn, does not contradict reasoning that is enlightened by the Qurʾān and Sunnah.